2018
DOI: 10.1111/ijd.14029
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of dermatitis herpetiformis from an immunobullous disease clinic in north India

Abstract: Dermatitis herpetiformis is not a rare disease in northern India as previously believed. The clinical, histological, and immunopathological characteristics of Indian DH patients are similar to those reported in Caucasian populations. The limitations of our study include an absence of genetic testing for HLA-DQ2 or DQ8, nonavailability of kits for detecting IgA specific for epidermal transglutaminase (IgA eTG), and short follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 19 publications
2
9
2
Order By: Relevance
“…The prevalence of prolonged skin symptoms in this study is rather high compared with our more recent study, in which only 13% of patients with DH were using dapsone after 2 years of adherence to a GFD ( 33 ). However, the few recent studies from other countries have reported that, despite strict adherence to a GFD, the majority of patients have been unable to stop dapsone during the first 2 years after diagnosis of DH ( 4 , 32 ), giving even a higher prevalence of prolonged skin symptoms than in the current study.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…The prevalence of prolonged skin symptoms in this study is rather high compared with our more recent study, in which only 13% of patients with DH were using dapsone after 2 years of adherence to a GFD ( 33 ). However, the few recent studies from other countries have reported that, despite strict adherence to a GFD, the majority of patients have been unable to stop dapsone during the first 2 years after diagnosis of DH ( 4 , 32 ), giving even a higher prevalence of prolonged skin symptoms than in the current study.…”
Section: Discussioncontrasting
confidence: 63%
“…Contemporary data concerning the duration of skin symptoms in DH after diagnosis and the onset of a GFD is scarce, and the few recent studies covering the subject have produced conflicting results ( 4 , 31 , 32 ). In the current study, 38% of patients with DH had skin symptoms enduring longer than 2 years after diagnosis and, among them, the majority (64 out of 69) were using dapsone longer than 2 years after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous lesions tend to heal without scarring, although post‐inflammatory hyper‐, or hypopigmentation may occur. In patients with darker skin types, the clinical presentation is similar to that seen in Caucasians 15,33 …”
Section: Diagnosticsmentioning
confidence: 72%
“…DH is now known to be a common extraintestinal manifestation of celiac disease occurring in up to 10% of the celiac disease patient series in Europe and North America [13][14][15]. Small DH series have also recently been described in Brazil, China, and India [16][17][18]. The incidence of DH has been shown to be decreasing [19,20], whereas the opposite is true for celiac disease, most likely because of improved awareness of subclinical cases and the wide use of serologic screening [21].…”
Section: Dermatitis Herpetiformis Linked To Celiac Diseasementioning
confidence: 99%